Peterson's principles of oral and maxillofacial surgery - Miloro, Michael; Ghali, G. E.; Larsen, Peter E.; Waite, Peter D. (Cham : Springer, 2022)
The new edition of this outstanding reference textbook, in two volumes, offers comprehensive and authoritative coverage of the contemporary specialty of oral and maxillofacial surgery. The aim is to provide an all-encompassing, user-friendly source of information that will meet the needs of residents and experienced surgeons in clinical practice and will also serve as an ideal companion during preparation for board certification or recertification examinations. All of the authors, numbering some 100, are distinguished experts in the areas that they address. The new edition takes full account of the significant changes in clinical practice and guidelines that have occurred during recent years. Readers will find clear explanations of the practical application of surgical principles, with a wealth of supporting illustrative material, including atlas-type illustrations to complement the descriptions of specific procedures. The fourth edition of Petersons Principles of Oral and Maxillofacial Surgery is a truly exceptional resource for clinicians and students alike. .
Wound Healing -- Medical Management and Preoperative Patient Assessment -- Pharmacology of Outpatient Anesthesia Medications -- Outpatient Anesthesia -- Impacted Teeth -- Pre-Prosthetic Surgery -- Pediatric Dentoalveolar Surgery -- Utilization of Three-dimensional Imaging Technology to Enhance Maxillofacial Surgical Applications -- Dynamic Navigation for Dental Implants -- Implant Prosthodontics -- The Science of Osseointegrated Implant Reconstruction -- Comprehensive Implant Site Preparation: Mandible -- A Graft-less Approach for Treatment of the Edentulous Maxilla: Contemporary considerations for Treatment planning, Biomechanical principles and surgical protocol -- Soft Tissue Management in Implant Therapy -- Craniofacial Implant Surgery -- Initial Management of the Trauma Patient -- Soft Tissue Injuries -- Rigid versus Nonrigid Fixation -- Dentoalveolar and Intraoral Soft Tissue Trauma -- Contemporary Management of Mandibular Fractures -- Fractures of the Mandibular Condyle -- Management of Maxillary Fractures -- Management of Zygomatic Complex Fractures -- Orbital and Ocular Trauma -- Management of Frontal Sinus and Naso-orbitoethmoid Complex Fractures -- Nasal Fractures -- Maxillofacial Firearm Injuries -- Paediatric Facial Trauma -- Management of Panfacial Fractures -- Differential Diagnosis of Oral Disease -- Odontogenic Cysts and Tumors -- Benign Nonodontogenic Lesions of the Jaws -- Oral Cancer: Classification, Diagnosis, and Staging -- Oral Cancer Management -- Lip Cancer -- Head and Neck Skin Cancer -- Salivary Gland Disease -- Mucosal and Related Dermatologic Diseases -- Pediatric Maxillofacial Pathology -- Odontogenic Infections -- Osteomyelitis, Osteoradionecrosis(ORN) and Medication Related Osteonecrosis of the Jaws(MRONJ) -- Local and Regional Flaps -- Nonvascularized Reconstruction -- Vascularized Reconstruction -- Microneurosurgery -- Comprehensive Management of Facial Clefts -- Alveolar Cleft Reconstruction -- Nonsyndromic Craniosynostosis -- Craniofacial Dysostosis Syndromes: Evaluation and Treatment of the Skeletal Deformities -- Technology in Oral and Maxillofacial Reconstruction -- Anatomy and Pathophysiology of the Temporomandibular Joint -- Nonsurgical Management of Temporomandibular Disorders -- Arthroscopy and Arthrocentesis of the Temporomandibular Joint -- Internal Derangement of the Temporomandibular Joint -- Hypomobility and Hypermobility Disorders of the Temporomandibular Joint -- Pediatric temporomandibular disorders: Juvenile Idiopathic Arthritis -- Vascularized Reconstruction -- Craniofacial Growth and Development -- Digital Data Acquisition and Treatment Planning in Orthognathic Surgery -- Orthodontics for Orthognathic Surgery -- Model Surgery and Computer-aided Surgical Simulation for Orthognathic Surgery -- Mandibular Orthognathic Surgery -- Maxillary Orthognathic Surgery -- Sequencing in Orthognathic Surgery -- Concomitant Orthognathic and Temporomandibular Joint Surgery -- Facial Asymmetry -- Soft Tissue Changes and Prediction with Orthognathic Surgery -- Complications in Orthognathic Surgery -- Cleft Orthognathic Surgery -- Distraction Osteogenesis of the Craniomaxillofacial Skeleton -- Surgical and Non-surgical Management of Obstructive Sleep Apnea -- Blepharoplasty -- Basic Principles of Rhinoplasty -- Rhytidectomy -- Forehead and Brow Procedures -- Otoplastic Surgery for the Protruding Ear -- Adjunctive Facial Cosmetic Procedures.
Includes index.
Online resource; title from PDF title page (SpringerLink, viewed August 22, 2022).
Keywords: Mouth -- Surgery; Maxilla -- Surgery; Face -- Surgery